2017
DOI: 10.1007/s11102-017-0805-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the microRNA 106b~25 cluster and its host gene MCM7 in corticotroph pituitary adenomas is associated with tumor invasion and Crooke’s cell morphology

Abstract: PurposeMCM7 (minichromosome maintenance complex component 7), a DNA replication licensing factor, is a host gene for the oncogenic miR-106b~25 cluster. It has been recently revealed as a relevant prognostic biomarker in a variety of cancers, including pituitary adenomas. The purpose of this study was to assess whether miR-106b~25 and MCM7 levels correlate with tumor invasiveness in a cohort of ACTH-immunopositive adenomas.MethodsTissue samples were obtained intraoperatively from 25 patients with pituitary aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 73 publications
(75 reference statements)
1
25
0
1
Order By: Relevance
“…both strands may be dysregulated concordantly in tumorigenesis 32 . For miR-145 and miR-30a 5p/3p pairs, analysis of RNAi and CRISPR screening data and miRNA-pathway interactions data across multiple cancer types showed they may regulate the survival/growth of numerous cancer cell lines by concordantly modulating the expression of cell cycle pathway genes.…”
Section: Resultsmentioning
confidence: 99%
“…both strands may be dysregulated concordantly in tumorigenesis 32 . For miR-145 and miR-30a 5p/3p pairs, analysis of RNAi and CRISPR screening data and miRNA-pathway interactions data across multiple cancer types showed they may regulate the survival/growth of numerous cancer cell lines by concordantly modulating the expression of cell cycle pathway genes.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] MiR‐106b‐5p is a mature form of miR‐106b, which is encoded by the miR‐106b‐25 cluster in the long arm 21 regions of human chromosome 7 (7q21). [ 33 ] The tumor specificity of miR‐106b‐5p has been broadly corroborated in all kinds of cancers. [ 34,35 ] Nonetheless, whether miR‐106b‐5p affects the roles of HOXA‐AS2 in sepsis‐evoked AKI remains unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidences have shown that miRNAs can target PD‐L1, thus altering the biological activities of tumors, such as invasion, migration, and immune evasion (Jia et al, 2017; Ashizawa et al, 2019). On the basis of the prediction of multiple online databases, we also found that PD‐L1 is a target gene of miR‐93‐5p, which is a member of the miR‐106b‐25 gene cluster that is abnormally expressed in various tumor tissues (Garbicz et al, 2017; Xiang et al, 2017). Previous evidence has identified the downregulation of miR‐93‐5p in CRC, suggesting the potential tumor‐suppressive role of miR‐93‐5p (Xiao et al, 2013; Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%